Plant microbiome responses to bioinoculants and volatiles - Expedito Olimi; Martina Duller; Martina Stangl; Samuel Bickel; Angelika Battisti; Peter Kusstatscher; Wisnu Adi Wicaksono; Ahmed Abdelfattah; Tomislav Cernava; Gabriele Berg (Environmental Microbiome)
Abstract Background There is an increase in the adoption of biological solutions for plant production as a means of attaining sustainable agriculture. A detailed understanding of the influence of specific bioinoculants and their volatile metabolites on native soil and plant microbiomes can improve future microbiome management practices. Results Here, we examined the effect of bacterial inoculants and volatile compounds as individual and combined treatments on apple plant and soil microbiome. The study used specially designed microcosms that facilitated the separation of the different plant compartments. A compartment- and soil-specific effect of treatments on the native soil and plant microbiome was observed. The live bacterial inoculants as compared to their volatiles had a stronger effect on the plant and soil microbiome, particularly the root microbial community. The combined effect of bacterial inoculants was higher compared to volatiles (R2 = 5% vs. 3%). Treatment-specific effects were observed, like the influence of 2-butanone on the phyllosphere bacterial diversity, and an increase in fungal richness in Serratia-treated soils. Conclusions Among the examined treatments, inoculation with bacteria compared to volatile metabolites induced more significant shifts within the plant and soil microbiome. This observation has implications regarding the merits of applying living microorganisms. The findings highlight the potential of microbiome management approaches for enhancing microbiota functions.